ANALISIS GHARAR PADA ENDORSMENT - Fitra, Audina (IAIN Parepare, 2024)
Gharar, in the context of Islamic law, refers to unwanted uncertainty or unclear risks in a transaction. In endorsements, the gharar factor may arise due to uncertainty regarding how the use of the celebrity will affect the perception and sales of the product.